New Insights on the Morphology of the Philippine Endemic Ficus pseudopalma Blanco - Victor Amoroso; Cristine Aser; Ann Villalobos; Rainear Mendez; Domingo Lodevico; Gina Barbosa (Journal of Tropical Life Science, 2022)
Ficus pseudopalma Blanco is an endemic Philippine plant with many medicinal uses and ethnobotanically as green vegetable or side dish. With these several economic uses of the plant, there is a need to investigate the morpho-anatomy and development of the species. Seeds of F. pseudopalma were collected in Mt. Hamiguitan Range Wildlife Sanctuary and grown in the Central Mindanao University Garden to monitor the growth and development of the species. Unique morpho-anatomical features were observed during its vegetative and reproductive development. Insights on the development of the syconia and seed formation are elucidated.